Distorsi Pasar; Solusi dalam Ekonomi Islam - Kumaidi, Kumaidi (Economic Reviews Journal, 2025)
The purpose of this study is to investigate market distortions in Islamic economic literature. In order to provide answers to the distortion issue, the investigation employs historical and philosophical methods. According to the study's findings, fraud (tadlis), uncertainty (taghrir), and demand and supply engineering (bai' najazy and ihtikar) are the main causes of distortion. Price regulation, market information disclosure, ikhtikar ban, and market intervention are the strategies used to combat market distortions.